2012
DOI: 10.1111/j.1365-2206.2012.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental resistance and social worker skills: towards a theory of motivational social work

Abstract: Parental resistance is a ubiquitous feature of child and family social work, yet there has been limited research or theoretical work directed at the issue. This paper identifies social and individual reasons why parents may be resistant. Five principle causes of parental resistance are discussed, namely social structure and disadvantage, the context of child protection work, parental resistance to change, denial or minimization of abuse or neglect and the behaviour of the social worker. It is argued that motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 37 publications
1
81
0
3
Order By: Relevance
“…Several factors were cited in the literature. The client-worker relationship is considered a key to enhancing parental cooperation (Forrester et al 2008(Forrester et al , 2012Gockel et al 2008;Lee and Ayon 2004;Maiter and Palmer 2006;Smith 2008;Trotter 2002Trotter , 2008. Holland (2000) found that the ability to agree on an explanation for the family situation is particularly important when determining the outcome of parental cooperation assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors were cited in the literature. The client-worker relationship is considered a key to enhancing parental cooperation (Forrester et al 2008(Forrester et al , 2012Gockel et al 2008;Lee and Ayon 2004;Maiter and Palmer 2006;Smith 2008;Trotter 2002Trotter , 2008. Holland (2000) found that the ability to agree on an explanation for the family situation is particularly important when determining the outcome of parental cooperation assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Where fathers do receive attention from the authorities, it may be as a potential abuser, in which case the tendency may be to exclude them from the family rather than to address the identified issue (Scott & Crooks 2004;Scourfield 2006). Where men are not excluded, they may be assessed as the source of undesirable behaviour without other needs being taken into consideration (Rivett 2010;Forrester et al 2012). In these circumstances, assessments may not accurately reflect the combination of factors men present for children they care for, potentially endangering children and excluding men.…”
Section: Background and Contextmentioning
confidence: 99%
“…This is partnered with another body of literature that recognises that an over-focus on investigation, risk and coercive intervention in child protection work has resulted in negative experiences (Dale, 2004;Dumbrill, 2006;Harris, 2011D.Scott, 2009) and outcomes for families (Forrester, Westlake & Glynn, 2012;Munro, 2011;Platt, 2008;Turney, 2012). Together these findings provide further support to the suggestion that the overuse of adversarial and coercive processes may in fact disempower and alienate families, preventing their active and willing engagement in change (Harnett & Day, 2008).…”
Section: Benefits and Challenges Of Collaborative Practicementioning
confidence: 66%
“…The literature indicates that the impact of statutory involvement on parents is often overlooked and as such, parent responses to the shock and trauma of statutory involvement, such as anger or disengagement, may be misinterpreted as risk factors for their ability to parent (Dumbrill, 2006;Forrester et al, 2012).…”
Section: "They Judge According To How the Family Communicates With Thmentioning
confidence: 99%
See 1 more Smart Citation